2007
DOI: 10.1136/qshc.2006.021154
|View full text |Cite
|
Sign up to set email alerts
|

Extent, nature and consequences of adverse events: results of a retrospective casenote review in a large NHS hospital

Abstract: Objectives: To estimate the extent, nature and consequences of adverse events in a large National Health Service (NHS) hospital, and to evaluate the reliability of a two-stage casenote review method in identifying adverse events. Design: A two-stage structured retrospective patient casenote review. Setting: A large NHS hospital in England. Population: A random sample of 1006 hospital admissions between January and May 2004: surgery (n = 311), general medicine (n = 251), elderly (n = 184), orthopaedics (n = 131… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
108
2
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 21 publications
5
108
2
6
Order By: Relevance
“…The data should not be interpreted as indicating the frequency of clinical complications, as only a small proportion of all clinical incidents or patient injuries lead to litigation [1][2][3][4]. We also lack denominator data meaning that high representation in this dataset might be due to high denominator rates or a disproportionate increase in claims for some incidents.…”
Section: ó 2009 the Authorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data should not be interpreted as indicating the frequency of clinical complications, as only a small proportion of all clinical incidents or patient injuries lead to litigation [1][2][3][4]. We also lack denominator data meaning that high representation in this dataset might be due to high denominator rates or a disproportionate increase in claims for some incidents.…”
Section: ó 2009 the Authorsmentioning
confidence: 99%
“…In 1991 Brennan [1] in America reported avoidable patient harm in 4% of hospitalisations, while in Australia in 1995 Wilson [2] reported adverse events in 17%. In the UK, in 2001, Vincent [3] reported iatrogenic harm in 11% of hospital admissions and in 2007 Sari [4] reported a 9% rate. Up to half of all these incidents are deemed 'avoidable' and many are associated with substandard or negligent care: around 1 in 10 contributes to patient death [1][2][3][4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since, further studies in the USA as well as in other countries, including the UK, have found similar and often slightly higher figures. [7][8][9][10][11][12] There is now available a wealth of research from different medical specialties and different countries that indicates that health care is a high-risk domain where patients may be harmed, for example in surgery 13,14 or medicines management and prescribing. 15,16 In addition to causing needless harm and suffering to patients, poor-quality health-care provision has significant financial implications for the health systems.…”
Section: Harm To Patientsmentioning
confidence: 99%
“…13,14 Isto é importante visto que o reconhecimento da ocorrência pelos profissionais de saúde é a base para o estabelecimento de uma cultura de segurança organizacional, com adoção de medidas de prevenção a eventos adversos. 15,16 Impulsionadas pela relevância da temática, um grupo de enfermeiras de um hospital universitário do sul do Brasil, atualmente acreditado pela JCI, percebeu a necessidade de identificar as ocorrências de incidentes de segurança na instituição e de analisá-las, a fim de implementar medidas de prevenção e favorecer a segurança dos pacientes. Somado a isto, o processo de acreditação pela JCI pelo qual passava o hospital reforçou esta necessidade, visto que o cuidado aos pacientes deve estar focado na realização de procedimentos de forma correta e com resultados efetivos, prevenindo riscos e reduzindo ou eliminando erros durante o processo de trabalho.…”
unclassified